Original paperAssessment of the efficacy of primary percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction based on the ECG analysis - Madżitow, Hikmat H.; Alimow, Donyor A. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background: The method of recording ECG is of particular importance for the diagnosis of cardiac arrhythmias, and an analysis of ST-segment behaviour, providing valuable information for the assessment of coronary circulation and the prognosis of patients with acute coronary syndrome. Aim : The objective of our study was to evaluate the effectiveness of reperfusion therapy with primary revascularization of the coronary artery responsible for myocardial infarction (infarct-related artery, IRA) in patients with acute myocardial infarction (AMI) with persistent ST-segment elevation in intraoperative ECG monitoring. Material and methods: The study included 72 patients (64 – 89% men) with anterior AMI who were hospitalized in order to perform primary angioplasty (primary PCI). Results : The average time from onset of pain to admission to hospital was 2.5 ±1.3 h. The average time from admission to start of treatment (pPCI) was 78.2 ±12.4 min. Effective treatment with primary PCI IRA stenting was performed in all 72 patients (100%) after initial recanalization and predilation. All patients achieved good angiographic results evaluated on the basis of the size of the residual stenosis (below 10%), while flow in the grade TIMI III was found in 62 (86.1%) treated patients. In 49 patients (68%) metal stents ("Chopin") were implanted, and in 23 (32%) other patients paclitaxel-eluting stents ("Luc-Chopin”) (Balton, Warsaw, PL) were implanted. ECG recording including the nature and frequency of arrhythmia was initiated prior to PCI. The measurements of changes in ST-segment elevation in relation to the isoelectric line were evaluated in the lead that best maps the changes in recording. Analysis of ECG monitoring results showed the characteristic dynamics of reduction of the ST level. Index rate of ST-segment depression after PCI was 3070.3 ±946.6 µV/h. In all cases with PCI there was reported the occurrence of arrhythmias after the reperfusion. Ventricular extrasystole (ExV) occurred in 72 patients (100%), accelerated idioventricular rhythm in 13 (18.0%), ventricular tachycardia in 14 (19.4)%, and ventricular fibrillation in 2 (2.7%). Through correlation analysis a significant association was detected between indicators of the speed of ST-segment depression after reperfusion, and left ventricular ejection fraction (LVEF), calculated 7 days after PCI (r = 0.53366, p < 0.001). Conclusions : 1) ECG monitoring is a study method of high clinical value, to evaluate the efficacy of reperfusion therapy in patients with AMI. 2) A significant correlation was detected between the rate of ST-segment depression after reperfusion and LVEF measured after 7 days of ACS with ST-segment elevation. 3) Index of ST-segment depression after reperfusion is a good predictor of restoration of left ventricular systolic function. 4) Primary PCI with stenting is an effective method of IRA reperfusion treatment of patients with AMI.